1982
DOI: 10.1111/j.1365-3059.1982.tb02809.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fungicide treatment on yield of winter wheat and spring barley cultivars

Abstract: Analyses of the results of 21 winter wheat and 32 spring barley trials showed that cultivars differed significantly in their yield response to a standard fungicide treatment. Responses were also strongly influenced by differences between sites and between years. Regression analyses showed that responses were significantly related to reductions in foliar disease, particularly that of mildew, although the proportion of variance accounted for was small. Measurements made on seven winter wheat trials indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…Yield responses to fungicide, where they occurred, varied between 6-3 and 11-8 %, within a similar range to yield responses in spring barley reported elsewhere (Priestley & Bayles 1982;Tonkin & Silvey 1982). Yield responses were accounted for by variations in green leaf area at GS79 in those experiments where they occurred.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Yield responses to fungicide, where they occurred, varied between 6-3 and 11-8 %, within a similar range to yield responses in spring barley reported elsewhere (Priestley & Bayles 1982;Tonkin & Silvey 1982). Yield responses were accounted for by variations in green leaf area at GS79 in those experiments where they occurred.…”
Section: Discussionsupporting
confidence: 67%
“…The relationship between yield response to fungicide and leaf area duration is well documented (James 1967;Priestley & Bayles 1982). In some cases, delayed leaf sensescence was not directly related to disease incidence, indicating some additional effect of fungicide other than disease control (Priestley & Bayles 1982;Wale & Hunter 1985). In the current work, disease incidence was not assessed directly, so any such effect could not be detected.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Delayed senescence of leaf tissue after fungicide application has also been reported in cereals (e.g., Priestley 1981;Priestley & Bayles 1982). However, the mechanism by which fungicides delay senescence is unclear.…”
Section: Introductionmentioning
confidence: 92%
“…With respect to the effect of honeydew on fungi, it has been demonstrated that the saprophytic phyllosphere mycoflora is able to antagonize infection by necrotrophic pathogens such as Septaria nodorum and Cochliobolus sativus and that this may neutralize negative effects of necrotrophic pathogens on yield (Fokkema et al, 1983). On the other hand, direct detrimental effects of saprophytes on cereal yield are occasionally suggested in attempts to explain unexpected yield increases in fungicide trials with low levels of naturally occurring pathogens (Dickingson and Walpole, 1975;Cook, 1981;Mappes and Hampel, 1977;Priestly and Bayles, 1982). To investigate the potentials of the saprophytes to suppress or reduce necrotrophic fungi through competition, more knowledge is urgently needed about the direct effects of saprophytes on necrotrophic fungi and on crop production in the field (Fokkema, 1981).…”
Section: Introductionmentioning
confidence: 99%